(4,7m²n+2,3mn-5n²)-(5,3mn-1,3m²n-5n²) = 4,7m²n+2,3mn-5n²-5,3mn+1,3m²n+5n² = 6m²n - 3mn = 3mn(2m-1)
a) m=1,n=5
3*1*5*(2*1-1) = 15
ответ: 15
б) m=-2,n=0,4
3*(-2)*0,4*(2*(-2) - 1) = 12
ответ: 12
Поделитесь своими знаниями, ответьте на вопрос:
Вычислить значение выражения. (4, 7m²n+2, 3mn-5n²)-(5, 3mn-1, 3m²n-5n²) а)при m=1, n=5 б)при m=-2, n=0, 4
(4,7m²n+2,3mn-5n²)-(5,3mn-1,3m²n-5n²) = 4,7m²n+2,3mn-5n²-5,3mn+1,3m²n+5n² = 6m²n - 3mn = 3mn(2m-1)
a) m=1,n=5
3*1*5*(2*1-1) = 15
ответ: 15
б) m=-2,n=0,4
3*(-2)*0,4*(2*(-2) - 1) = 12
ответ: 12